Antibacterial Potential of Ajwa Seed (Phoenix dactylifera L.) Ethanol Extract Mouthwash Preparation Against Porphyromonas gingivalis - Etny Dyah Harniati; Retno Kusniati; Siti Aminah; Yasinia Annisa Prubomurti; Amelia Dwi Rustanti (Jurnal Kesehatan Gigi, 2026)
Chronic periodontitis, primarily caused by Porphyromonas gingivalis, often requires adjunctive mouthwash therapy. While Chlorhexidine is the gold standard, its long-term use leads to various side effects. Date seeds, containing active compounds like polyphenols, flavonoids, and tannins, offer potential as a natural, environmentally friendly antibacterial alternative against Porphyromonas gingivalis. Research Objectives: This study aimed to develop and evaluate a date seed extract-based mouthwash for its effectiveness against Porphyromonas gingivalis growth. The experimental design tested three extract concentrations (5%, 7.5%, and 10%) for antibacterial activity. Phytochemical screening identified active compounds, and antibacterial testing was conducted using the agar diffusion method. showed date seed extract contains secondary metabolites such as alkaloids, flavonoids, tannins, and steroids, indicating antibacterial potential. The formulated mouthwash had a liquid, brownish texture with a characteristic aroma, though it produced undissolved precipitates. Importantly, antibacterial testing demonstrated significant inhibitory capability against Porphyromonas gingivalis, evidenced by clear inhibition zones, with a significant difference (p < 0.001) in diameter across concentrations. In conclusion, Ajwa date seeds effectively inhibit Porphyromonas gingivalis growth. A higher concentration of date seed extract in the mouthwash formula results in greater inhibitory power